Unlocking Fluent Speech: Enhancing Student Speaking Skills through Digital Storytelling - Zizi Nurhikmah (Journal of English Teaching and Applied Linguistics, 2024)
This study evaluates the impact of digital storytelling on improving college students' speaking skills, based on Vygotsky’s Social Constructivism, which emphasizes the role of social interaction and cultural tools in learning.